High-efficiency subnanosecond microwave pulse generation in a relativistic backward wave tube; Technical Physics Letters; Vol. 28, iss. 1 - Korovin S. D.; Mesyats G. A. Gennady Andreyevich; Rostov V. V.; Ul'maskulov M. R.; Sharypov K. A.; Shpak V. G.; Shunailov S. A.; Yalandin M. I. (2002, 2002)
Title screen